Performance of the tunnel boring machine TBM vs. rock type - Giraldo Paredez, Emiliano (2009)
The tunnel boring machines (TBM) are continuous mining equipment designed for the excavation of circular tunnels until more than 15 m of diameter at the moment. The application of these machines in substitution of the conventional drilling and blasting method, is more and more frequent, including in our country, since from the first application in the Carhuaquero project (Chiclayo) at beginnings of the decade of 1980, spent almost 18 years for the following application in the Chimay project (1998-1999); soon between years 2000-2004 in hydroelectric project of Yuncan, they were applied to 2 TBM (only a year after the application in Chimay) and at the moment in the project it trasvase Elm trees, comes applying a TBM from the 2007. It demonstrates without a doubt, that the application of the TBMs is prominent in the present century. This article is based on the study made in the hydroelectric project of Yuncan, to TBM MK 12 during almost 2 years (from its assembly to its operation). In this project, this TBM worked with a diameter of 4.10 ms, during the excavation crossed different types of rocks, predominating among them the altered rock that added to the great water affluence, had low yields of this TBM, being reversed the greater time in support of the rock, including some days without advance some.